Analysis of The Behavior of Traditional Market Traders in The Perspective of Islamic Business Ethics - Kurniawan, Heri; Qarni, Waizul; Nasution, Muhammad Lathief Ilhamy (Universitas Trunojoyo Madura, 2024)
This research is very important because it will help because evaluating the actions of conventional market traders in Natal from the point of view of Islamic business ethics shows honesty, integrity and kindness in your work. In addition, this activity can help consumers and traders do business better. The purpose of this study is to gain a better understanding of the needs of traders from the point of view of business practices. Islam targeting traditional markets in the Natal region.The research area was traditional markets in Natal. Data were collected through descriptions, interviews, observations and documents. Verification of data validity using more power, references, and visual indicators. The research shows that traders in traditional markets in Natal conduct buying and selling trade despite not knowing the principles of Islamic trade. They use rules such as not forgetting the truth and balance, not hiding mistakes, giving customers the freedom to choose, we must follow Islamic business principles, such as keeping promises, being responsible for product quality, and providing friendly services.